Food Supply Chain Network (FSCN) Analysis of Traditional Smoked Fish Enterprises in Bone Regency: Structure and Risks - Dian Islamia Muhtar; A. Nadia Mughsita Sani; Muhammad Yusfi Yusuf; Ardy Andreas Bernard Kase; Yushra Yushra; Taufiq Ahmad Romdoni; Nurmaida Nurmaida (Torani Journal of Fisheries and Marine Science, 2026)
Traditional smoked fish enterprises play an important role in supporting the livelihoods of coastal communities. However, the highly perishable nature of fish products poses significant challenges to the supply chain, including uncertainty in raw material availability, limited coordination among supply chain actors, and distribution risks. This study aimed to analyse the Food Supply Chain Network (FSCN) of traditional smoked fish enterprises in Bone Regency, Indonesia, by examining the network structure, supply chain management, business processes, resources, product, information, and financial flows, as well as identifying key bottlenecks and supply chain risks. A descriptive research approach was employed through field observations and interviews with 38 traditional smoked fish producers selected using the census method as the primary respondents. The analysis was further supported by information obtained from other supply chain actors to provide a comprehensive FSCN assessment. The results revealed that the smoked fish supply chain consists of five main actors: fishers, raw material suppliers, smoked fish producers, retailers, and end consumers, supported by secondary actors providing production facilities and supporting services. Smoked fish producers serve as the central actors by transforming fresh fish into value-added smoked fish products. Product flows move from fishers and suppliers to producers and subsequently to retailers and end consumers. Information flows occur bidirectionally among supply chain actors, while financial flows move upstream from consumers through predominantly cash-based transactions founded on mutual trust. The business processes encompass raw material procurement, production, inventory replenishment, and customer order fulfilment. FSCN analysis identified raw material supply as the primary key bottleneck, primarily due to dependence on capture fisheries, where seasonal variation and adverse weather conditions disrupt the continuity of fresh fish supply. This bottleneck is further exacerbated by limited processing technology and quality deterioration during product distribution. These findings highlight the importance of strengthening raw material supply continuity, enhancing coordination among supply chain actors, and improving institutional integration to increase the resilience and sustainability of the traditional smoked fish supply chain in Bone Regency